Why we die : the new science of aging and the quest for immortality - Ramakrishnan, Venki, 1952- (William Morrow, an imprint of HarperCollins Publishers, 2024)
"A groundbreaking exploration of the science of why and how we age and die-from Nobel Prize-winning molecular biologist Venki Ramakrishnan"--